Kiss of the dragon. - Nahon, Chris (New Manila, Quezon City : Viva Video, 2001)
International martial arts phenomenon Jet Li (Romeo Must Die, Lethal Weapon 4, The Legend) stars with Bridget Fonda (Jackie Brown, Monkeyone, Singles) in an unstoppably exciting thriller where deadly intrigue meets hard-hitting action! Li plays Liu Juan, China's top government agent, who travels to Paris on a sensitive, top-secret mission. But when he arrives, Liu become trapped on the wrong side of a vast and lethal conspiracy orchestrated by the powerful police official (Tcheky Karyo - The Patriot, Saving GRacce, My Life So Far) he was sent to assist! With nowhere to turn in a city he doesn't know, Liu is thrown together with an American Woman, Jessica (Fonda), who shares the same ruthless adversary! As you thrill to the incomparable Jet Li performing all of his own incredible fight scenes, the action explodes from the screen as Liu and Jessica boldly take on the force that seeks to take them out!